2009
DOI: 10.1111/j.1523-536x.2009.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

“Universal Precautions”: Perinatal Touch and Examination after Childhood Sexual Abuse

Abstract: Childhood sexual abuse survivors experienced pain, dissociation, fear, blame, helplessness, and guilt in their encounters with health care practitioners. These experiences led to the development of a set of "Universal Precautions" for perinatal professionals responding to women and their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(141 citation statements)
references
References 26 publications
3
137
0
1
Order By: Relevance
“…The most common suggestions for mitigating distress given by survivors were assessing whether patients feel comfortable (Coles & Jones, 2009;Muzik et al, 2013) and allowing for breaks or stopping procedures when patients feel overwhelmed (Coles & Jones, 2009;Dunleavy & Kubo Slowik, 2012;Roberts et al, 1999;Seng & Hassinger, 1998). Similarly, Averbuch and Spatz (2009) recommend that postpartum nurses provide reassurance and support to female survivors of sexual abuse in stopping breastfeeding if they find the associated sensations distressing (Averbuch & Spatz, 2009).…”
Section: Minimizing Distress and Maximizing Autonomymentioning
confidence: 91%
See 3 more Smart Citations
“…The most common suggestions for mitigating distress given by survivors were assessing whether patients feel comfortable (Coles & Jones, 2009;Muzik et al, 2013) and allowing for breaks or stopping procedures when patients feel overwhelmed (Coles & Jones, 2009;Dunleavy & Kubo Slowik, 2012;Roberts et al, 1999;Seng & Hassinger, 1998). Similarly, Averbuch and Spatz (2009) recommend that postpartum nurses provide reassurance and support to female survivors of sexual abuse in stopping breastfeeding if they find the associated sensations distressing (Averbuch & Spatz, 2009).…”
Section: Minimizing Distress and Maximizing Autonomymentioning
confidence: 91%
“…Female survivors of child and adult sexual abuse in numerous settings and studies stated that being asked for their verbal consent by providers in health care settings before examinations or procedures made them feel more comfortable and in-control (Aaron et al, 2013;Coles & Jones, 2009;Muzik et al, 2013;Roberts et al, 1999). Female CSA survivors in Coles and Jones' study suggested that providers should ask for consent before beginning care and at points of transition between different steps and procedures.…”
Section: Minimizing Distress and Maximizing Autonomymentioning
confidence: 95%
See 2 more Smart Citations
“…Por tanto, la práctica de la enfermería debe estar centrada en el cuidado, con respaldo del conocimiento, en el diálogo y en el establecimiento de relaciones interpersonales satisfactorias, y basada en actitudes y habilidades en la promoción de un ambiente seguro, al poder promover cuidados sin que haya ocurrencia de daños y, por ello, una sensación de seguridad (7,(17)(18)(19) .…”
Section: Nº 35 Julio 2014unclassified